DETERMINE THE POLICY TARGET TO INCREASE INSTITUTIONAL DELIVERY AMONG INDONESIAN FEMALE WORKERS - Syahri, Isyatun Mardhiyah; Laksono, Agung Dwi; Fitria, Maya; Rohmah, Nikmatur; Lolong, Dina Bisara; Alruwaili, Abdulah Saleh (Universitas Airlangga, 2024)
Introduction: Indonesia continues to face a significant challenge in terms of maternal and infant mortality. The government is working to promote the use of health facilities for childbirth to mitigate maternal mortality. Aim: The study aims to determine the policy target to increase the rate of institutional delivery among female workers in Indonesia. Methods: The study analyzed secondary data from the 2023 Indonesian Health Survey. It conducted cross-sectional research on 30,173 female workers. In addition to institutional delivery as the dependent variable, we examined eight independent variables: residence, age, education, marital status, wealth, insurance, antenatal care (ANC), and parity. The analysis involved bivariate method followed by binary logistic regression in the last stage. Results: Approximately 70.6% of female workers had institutional delivery. Female workers in urban areas were 1.157 times more likely than rural workers to perform institutional delivery (95%CI 1.153-1.161). Three worker characteristics (age, education, and marital status) were related to institutional delivery. Wealthier workers had a greater the possibility of executing institutional delivery. Insured workers were more likely than the uninsured ones to deliver in health facilities. Female workers with adequate ANC were 1.210 times more likely than those with inadequate ANC to execute institutional delivery (95%CI 1.166-1.256). Additionally, women with fewer childbirths had a higher probability of performing an institutional delivery. Conclusion: The policy target to increase institutional delivery was women workers in rural areas who were older, had poor education, were divorced/widowed, were the poorest, had inadequate ANC, were uninsured, and were grand multiparous. Keywords: institutional delivery, institutional birth, maternal health, female worker, public health.